Soft β_Compactnees in Soft Topological Spaces (Latakia University Journal -Basic Sciences Series, 2020)
In this paper, first of all-we show the notion of soft sets and its relationhips(null soft set, absolute soft set, complement of a soft set, the operations of union, intersection….etc)Also, we show the notion of  soft Topological Spaces, we study many types of soft open sets (soft preopen set, soft semi open set, soft β-open set) with exampels.Second,we show several types of soft  Compactness in soft Topological Spaces, and study the relationship between them.Finally, we investigate more properties of soft β_Compactness in soft Topological Spaces and consider  their behaviour under certain soft mapping.